Taḥyâ as-sînamâ ! Produire du sens : les enjeux politiques de l’expression dans l’espace public - Cécile Boëx (Revue des Mondes Musulmans et de la Méditerranée)
This article focuses on the political stakes involved into public expression in Syria and more specifically artistic expression, through the lens of the most recent film festival of Damascus. This event is particularly relevant of the different ways culture and artistic production can be co-opted by political interest. This particular approach will enable us to cast light on the attempts of an authoritarian regime to control the production of meaning and impose its interpretation of events. We will demonstrate that this context has not prevented dissenting expressive practices, embedded in various strategies of circumvention. We will illustrate these practices through examples form different registers: the last demonstrations against the Mehlis investigation, and cinematographic expression, which has played a leading role in bringing dissension into the public sphere.